INVESTIGATION OF SINGLE-PASS/DOUBLE-PASS TECHNIQUES ON FRICTION STIR WELDING OF ALUMINIUM - N.A.A. Sathari; L.H. Shah; A.R. Razali (Journal of Mechanical Engineering and Sciences, 2014)
The aim of this research is to study the effects of single-pass/ double-pass techniques on friction stir welding of aluminium. Two pieces of AA1100 with a thickness of 6.0 mm were friction stir welded using a CNC milling machine at rotational speeds of 1400 rpm, 1600 rpm and 1800 rpm respectively for single-pass and double-pass. Microstructure observations of the welded area were studied using an optical microscope. The specimens were tested by using a tensile test and Vickers hardness test to evaluate their mechanical properties. The results indicated that, at low rotational speed, defects such as ‘surface lack of fill’ and tunnels in the welded area contributed to a decrease in mechanical properties. Welded specimens using double-pass techniques show increasing values of tensile strength and hardness. From this investigation it is found that the best parameters of FSW welded aluminium AA1100 plate were those using double-pass techniques that produce mechanically sound joints with a hardness of 56.38 HV and 108 MPa strength at 1800 rpm compared to the single-pass technique.